Assessment of trace element accumulation in surface sediments off Chennai coast after a major flood event. Issue 2 (30th January 2017) - Gopal, V.; Krishnakumar, S.; Simon Peter, T.; Nethaji, S.; Suresh Kumar, K.; Jayaprakash, M.; Magesh, N.S.
Abstract: The present study was conducted to assess the trace element concentration in marine surface sediments after major flood event of Chennai metropolis, India. Thirty surface samples were collected from off Chennai coast. Trace elements, organic matter, CaCO3, sand-silt-clay and C/N ratios were studied to understand the accumulation dynamics on sediments. The elemental concentration, calcium carbonate and OM distribution suggest that they are derived from urban runoff and transported through Adyar and Cooum Rivers. The enrichment factor reveals that the sediments are enriched by Pb, Cu, Zn, Cr, Co, Ni followed by Fe. The observed Igeo value shows that the samples are contaminated by Pb, Cu and Zn. The elemental concentration of the surface sediments is low when compared to other coastal region except Pb. The elevated level of Pb in the surface sediments is probably due to migration of contaminated urban soil from industrial and transportation sectors into marine environment. Highlights: The distribution of trace elements is controlled by urban runoff and riverine input. The concentration of lead is contributed from application of leaded petrol. The long shore sediment transport is responsible for distribution of elements along the coast.